Overexpression of blaOXA-58 Gene Driven by ISAba3 Is Associated with Imipenem Resistance in a Clinical Acinetobacter baumannii Isolate from Vietnam. (3rd August 2020) - Nguyen, Anh T.; Pham, Son C.; Ly, Anh K.; Nguyen, Chau V. V.; Vu, Thanh T.; Ha, Tuan M.
Abstract : The aim of this study was to investigate genetic structures and expression of bla OXA-58 gene in five Acinetobacter baumannii clinical isolates recovered from two hospitals in southern Vietnam during 2012-2014. A. baumannii isolates were identified by automated microbiology systems and confirmed by PCR. All isolates were characterized as multidrug resistant by antimicrobial testing using the disk diffusion method. Four imipenem susceptible and one nonsusceptible isolates (MIC > 32 μ g ·ml -1 ) were identified by E-test. PCR amplification of bla OXA-58 gene upstream and downstream sequences revealed the presence of IS Aba3 at both locations in one multidrug-resistant isolate. Semiquantitation of bla OXA-51 and bla OXA-58 gene expression was performed by the 2 - ΔΔ Ct method. The bla OXA-51 gene expression of five isolates showed little difference, but the isolate bearing IS Aba3 - bla OXA-58 -IS Aba3 exhibited significantly higher bla OXA-58 mRNA level. Higher β -lactamases activity in periplasmic than cytoplasmic fraction was found in most isolates. The isolate overexpressing bla OXA-58 gene possessed very high periplasmic enzyme activity. In conclusion, the A. baumannii isolate bearing IS Aba3 - bla OXA-58 gene exhibited high resistance to imipenem, corresponding to an overexpression of bla OXA-58 gene and very high periplasmic β -lactamase activity.